Establishment of a placental lncRNA-mRNA expression network for early-onset preeclampsia - Ya Chen; Ying Zhang; Siyu Xie; Xiangdong Zhou; Lina Zhu; Yunxia Cao (BMC, 2024)
Abstract Background This study aimed to establish a placental long non-coding RNA (lncRNA)-mRNA expression network for early-onset preeclampsia (early-onset PE). Methods The RNA sequencing data of the GSE14821 dataset were acquired. Several crucial lncRNAs and mRNAs were exerted based on the differential expression analysis of lncRNA and mRNA. By analyzing the differentially expressed lncRNA and mRNA, we constructed a regulatory network to explore the mechanism of the lncRNA in early onset preeclampsia. Results A total of 4436 differentially expressed lncRNAs (DElncRNAs) were identified in early-onset PE placenta samples compared with control placenta samples. Pearson correlation analysis revealed significant correlations between 3659 DElncRNAs and 372 DEmRNAs. KEGG analysis showed that the DEmRNAs were enriched in cytokine-cytokine receptor and hypoxia-inducible factor (HIF)-1 pathways. Several well-known early-onset PE-related mRNAs, such as vascular endothelial growth factor A (VEGFA) and VEGF receptor 1 (FLT1), were involved in the two pathways. Weighted gene co-expression network analysis and cis-regulatory analysis further suggested the involvement of the two pathways and potential DElncRNA-DEmRNA interactions in early-onset PE. Moreover, the upregulation of representative DElncRNAs, such as RP11-211G3.3 and RP11-65J21.3, and DEmRNAs, such as VEGFA and FLT1, were validated in clinical placenta samples from patients with early-onset PE by quantitative reverse transcription PCR. Importantly, overexpression of RP11-65J21.3 significantly promoted the proliferation of HTR-8 trophoblast cells at 72 h after transfection. Conclusions In conclusion, we identified placental DElncRNAs of early-onset PE and established a DElncRNA-DEmRNA network that was closely related to the cytokine-cytokine receptor and HIF-1 pathways. Our results provide potential diagnostic markers and therapeutic targets for early-onset PE management.